MiR‐181a/b control the assembly of visual circuitry by regulating retinal axon specification and growth. Issue 11 (11th June 2015) - Carrella, Sabrina; D'Agostino, Ylenia; Barbato, Sara; Huber‐Reggi, Sabina P.; Salierno, Francesco G.; Manfredi, Anna; Neuhauss, Stephan C.F.; Banfi, Sandro; Conte, Ivan
ABSTRACT Connectivity and function of neuronal circuitry require the correct specification and growth of axons and dendrites. Here, we identify the microRNAs miR‐181a and miR‐181b as key regulators of retinal axon specification and growth. Loss of miR‐181a/b in medaka fish (Oryzias latipes) failed to consolidate amacrine cell processes into axons and delayed the growth of retinal ganglion cell (RGC) axons. These alterations were accompanied by defects in visual connectivity and function. We demonstrated that miR‐181a/b exert these actions through negative modulation of MAPK/ERK signaling that in turn leads to RhoA reduction and proper neuritogenesis in both amacrine cells and RGCs via local cytoskeletal rearrangement. Our results identify a new pathway for axon specification and growth unraveling a crucial role of miR‐181a/b in the proper establishment of visual system connectivity and function. © 2015 Wiley Periodicals, Inc. Develop Neurobiol 75: 1252–1267, 2015